2011
DOI: 10.5334/pb-51-2-139
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gaze Direction on Face Recognition: A Sensitive Effect

Abstract: This study was aimed at determining the conditions in which eye-contact may improve recognition memory for faces. Different stimuli and procedures were tested in four experiments. The effect of gaze direction on memory was found when a simple "yes-no" recognition task was used but not when the recognition task was more complex (e.g., including "Remember-Know" judgements, cf. Experiment 2, or confidence ratings, cf. Experiment 4). Moreover, even when a "yes-no" recognition paradigm was used, the effect occurred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…We hypothesize that these longer reaction times potentially reflect a deeper cognitive elaboration throughout the study, with participants being more uncertain about the accuracy of their answer, since they never received any confirmation. Relevant to this issue is the finding that the memory bias for faces depicting direct gaze (e.g., Mason, Hood, & Macrae, 2004; Nakashima, Langton, & Yoshikawa, 2012) is affected by task instruction (Daury, 2011). Whereas a simple “old/new” task elicited a bias for faces with direct gaze, a more elaborate “remember/know/guess” task eliminated this effect.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that these longer reaction times potentially reflect a deeper cognitive elaboration throughout the study, with participants being more uncertain about the accuracy of their answer, since they never received any confirmation. Relevant to this issue is the finding that the memory bias for faces depicting direct gaze (e.g., Mason, Hood, & Macrae, 2004; Nakashima, Langton, & Yoshikawa, 2012) is affected by task instruction (Daury, 2011). Whereas a simple “old/new” task elicited a bias for faces with direct gaze, a more elaborate “remember/know/guess” task eliminated this effect.…”
Section: Discussionmentioning
confidence: 99%
“…For example, many studies have claimed that direct-gaze faces draw attention towards themselves whereas faces with an averted gaze draw attention to the place they look at [8][9][10]94]. Several reports have suggested that gaze is a relevant cue for the recognition of gender, age, and emotional expression in a face [44,95,96], especially when gaze makes eye contact, as it provides a processing advantage that makes face detection faster [10,97]; this advantage is known as the eye-contact effect.…”
Section: Gaze Directionmentioning
confidence: 99%
“…For example, while direct-gaze faces draw attention towards themselves, faces with an averted gaze draw attention to the place they look at [7][8][9]81]. Several reports have suggested that gaze is a relevant cue for the recognition of gender, age, and emotional expression in a face [31,82,83], especially when gaze makes eye contact, as it provides a processing advantage that makes face detection faster [9,84]; this advantage is known as the eye-contact effect.…”
Section: Gaze Directionmentioning
confidence: 99%